Statistical analysis plan for the OPTIMUM study: optimising immunisation using mixed schedules, an adaptive randomised controlled trial of a mixed whole-cell/acellular pertussis vaccine schedule - Totterdell, J.A.; Chacon, G.P.; Estcourt, M.J.; Jones, M.; Richmond, P.; Snelling, Tom; Marsh, J.A. (2022)
Objective: The purpose of this double-blind, randomised, controlled trial is to compare allergic outcomes in children following vaccination with acellular pertussis (aP) antigen (standard of care in Australia) given at 2 months of age versus whole cell pertussis (wP) in the infant vaccine schedule. Participants: Up to 3000 Australian infants 6 to <12 weeks of age born ≥32 weeks gestation. Interventions: The intervention is a wP containing vaccine as the first scheduled pertussis vaccine dose instead of an aP containing vaccine. Outcomes: The primary outcome is a binary indicator of history of IgE-mediated food allergy at the age of 12 months confirmed, where necessary, with an oral food challenge before 18 months of age. Secondary outcomes include (1) history of parent-reported clinician-diagnosed new onset of atopic dermatitis by 6 or 12 months of age with a positive skin prick test to any allergen before 12 months of age, (2) geometric mean concentration in pertussis toxin-specific IgG before and 21 to 35 days after a booster dose of aP at 18 months of age, and (3) sensitisation to at least one allergen by 12 months of age. Results: Operating characteristics of trial decision rules were evaluated by trial simulation. The selected rules for success and futility approximately maintain type I error of 0.05 and achieved power 0.85 for a reduction in the primary outcome from 10% in the control group to 7% in the intervention group. Discussion: A detailed, prospective statistical analysis plan (SAP) is presented for this Bayesian adaptive design. The plan was written by the trial statistician and details the study design, pre-specified adaptive elements, decision thresholds, statistical methods, and the simulations used to evaluate the operating characteristics of the trial. Application of this SAP will minimise bias and supports transparent and reproducible research. Trial registration: Australia & New Zealand Clinical Trials Registry, ACTRN12617000065392. Registered on 12 January 2017 Study protocol: https://doi.org/10.1136/bmjopen-2020-042838